Storytelling Activities of the Story of Prophet Ayub AS at RA Dewi Masyithoh for the Formation of Children's Religious Characters in the Golden Age Phase (Equilibrium: Jurnal Pendidikan, 2022)
Early childhood is the "golden era" because children's physical, motor, emotional, intellectual, and moral qualities develop rapidly. Coaching is carried out through education levels from birth to the age of six years to optimize the growth and development of early childhood, one of which is religious character education as a provision for a better life as the nation's next generation. Religious characters are crucial to cultivating because they have a better absorption capacity and have not been corrupted by harmful cultural influences that are not in line with the nation's character. Using storytelling activities on the stories of the prophets, particularly about the prophet Ayub AS, is one technique to inculcate religious character. This study aimed to identify the elements that supported and inhibited the formation of religious characters in children during the golden age era through tale-telling activities about the Prophet Ayub AS at RA Dewi Masyithoh. This study is a sort of qualitative study that employs observation, interviews, and documentation as tools. The preparation, implementation, and evaluation stages of the research on the formation of religious characters through storytelling activities for the story of the prophet Ayub AS include the preparation, implementation, and evaluation stages; the supporting factors for this research are teachers in general already know adequate learning strategies to carry out learning; early childhood likes to listen to stories, especially the story of the prophet; the inhibiting factor is not all teachers have knowledge about storytelling effective learning strategies to carry out learning; and the inhibiting factor is not all teachers know about adequate education.
Keywords: Religious Character; Storytelling; Story of the Prophet Ayub AS